2017
DOI: 10.5664/jcsm.6504
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Obstructive Sleep Apnea and Its Treatments on Partners: A Literature Review

Abstract: Study Objectives: Many adults sleep with a significant other; thus, sleep disorder symptoms and treatments of one partner are likely to impact the other partner's health. A literature review was conducted to examine the impact of obstructive sleep apnea (OSA) and OSA treatments on partner-assessed sleep and daytime functioning and partner involvement in OSA treatment. Methods: MEDLINE, EMBASE, and CINAHL searches yielded 38 pertinent quantitative and qualitative studies that described sleep and/or daytime func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(33 citation statements)
references
References 64 publications
1
31
0
1
Order By: Relevance
“…Our findings are all the more important when looking at recent studies showing an association between OSAS and quality of life of bed partners. [ 27 28 ] These people are, in fact, exposed to a loud and frequent sound that can cause a noise-induced hearing loss. [ 29 30 ]…”
Section: Discussionmentioning
confidence: 99%
“…Our findings are all the more important when looking at recent studies showing an association between OSAS and quality of life of bed partners. [ 27 28 ] These people are, in fact, exposed to a loud and frequent sound that can cause a noise-induced hearing loss. [ 29 30 ]…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, this method can be used with an embedded real-time system because it effectively reduces computational power requirements by focusing on time-domain features within 130 s window frames, requiring less signal processing in feature extraction, applying a dynamic threshold to adapt to real-time signal changes, and, most importantly, shortening the time required to build a fuzzy logic model without a training process. Reports have indicated that portable monitors measuring three or more physiological parameters (level 3 and level 2 monitoring) offer accurate results in comparison with laboratory results [35][36][37][38][39]. Due to the fact that discomfort and inconvenience are barriers to the prevalence of PSG among the public, a single-channel airflow signal is one of the most applicable solutions for real-time monitoring [32,37,38].…”
Section: Discussionmentioning
confidence: 99%
“…Due to the fact that discomfort and inconvenience are barriers to the prevalence of PSG among the public, a single-channel airflow signal is one of the most applicable solutions for real-time monitoring [32,37,38]. OSAHS has serious and life-shortening consequences including cardiovascular disease, diabetes, poor quality of life, depression, and automobile accidents caused by falling asleep [39]. However, waiting times for PSG diagnosis in the United States and United Kingdom were estimated to be 2-10 and 7-60 months, respectively [40].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5,6 Obstructive Sleep Apnea Airway collapses during the sleep cycle, preventing normal breathing, causing lack of oxygen to the brain, preventing the individual from reaching deep sleep along with body and brain repair. 1,5,6,13,14 Poor memory processing, poor emotion processing [2][3][4][5][6]9,12,37 out of the deep stages of sleep, they are prevented from obtaining rejuvenation of the body and brain needed to achieve or maintain optimal health. 1,2 Sleep arousals can be caused by poor sleep hygiene, restricted airway, systemic health issues, or cognitive health issues.…”
Section: Circadian Rhythm Disruptionsmentioning
confidence: 99%